Topoclimatologia no Cânion Itaimbezinho, bacia hidrográfica do Rio do Boi - RS/SC - Baratto, Jakeline (2021)
The paper aims to analyze the influence of the relief as a climatic control on the variability of temperature, relative humidity, the genesis of fogs and the occurrence of occult precipitation in the Rio do Boi watershed, RS/SC. The study area is inserted into the Aparados da Serra National Park (PNAS) and its Buffer Zone. PNAS is an important environment for the preservation or conservation of the local fauna and flora. An automatic weather station, seven low-cost weather shelters (ABC model) and three fog collectors were used to develop this research. The shelters and collectors were installed at different elevations in the study area. Data sampling period comprehended from November 2017 to December 2018. Data analysis was performed using statistical techniques (correlation coefficients (r) and coefficients of determination (R²) and linear regression) to establish the relationship between weather shelter data and altitude. The relationship between the contribution of topography and climatic attributes on the occult precipitation were established using some techniques and data analysis. First, the hourly occult precipitation records were selected based on the rainfall data. Thus, the hours when only the fog collector recorded were considered as occult precipitation events. After this selection, the occult precipitation data were organized into monthly, seasonal, and annual totals. The topoclimatic units were delineated by relating the climatic attribute to the climatic controls. Results showed that altitude is an important controller of air temperature and absolute air humidity measurements. However, the orientation of the slope was also an important contributor to its variation. The water collected by the fog collector was quite expressive for the Rio do Boi watershed. The occult precipitation events occurred mainly at night. These events relate in the reduction of the air temperature to the dew point temperature. The occult precipitation events occurred in weather conditions associated with polar systems, predominantly. Six climate units were selected. They were delimited due to the different interactions between the climatic attributes and the climatic controls observed also in the field work. Therefore, the configuration of the relief was responsible for the climatic dynamics of the Rio do Boi watershed. The relief also provides favorable conditions for the formation of fog and consequently the recording of hidden precipitation. The additional water from the watershed favors the input of nutrients for plants and soil. Thus, it contributes to the development of ecosystems.